2019
DOI: 10.3389/fmicb.2019.00283
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Antibiotic Susceptibility, and Molecular Characterization of Cronobacter spp. Isolated From Edible Mushrooms in China

Abstract: Cronobacter spp. are foodborne pathogens that can infect and cause life-threatening diseases in all age groups, particularly in infants and immunocompromised elderly. This study aimed to investigate the prevalence, antibiotic susceptibility, and molecular characteristics of Cronobacter spp. isolates in edible mushrooms collected from 44 cities in China. In total, 668 edible mushrooms were collected from traditional retail markets and supermarkets and were analyzed by quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 58 publications
2
25
1
2
Order By: Relevance
“…The Cronobacter genus including seven species are opportunistic foodborne human pathogens that can cause rare but serious diseases in neonates and immune-compromised infants (Iversen et al, 2008; Kucerova et al, 2011; Joseph et al, 2012a). In our previous studies, C. sakazakii , C. malonaticus , and C. dublinensis were three prevalent species in food, however, we have never isolated C. universalis and C. condimenti strains (Xu et al, 2015; Ling et al, 2018; Li et al, 2019). In total, five C. turicensis and one C. muytjensii strains were isolated from vegetables and ready-to-eat foods (Xu et al, 2015; Ling et al, 2018) and we have successfully performed CRISPR arrays on these isolates using the same primers used for C. sakazakii .…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The Cronobacter genus including seven species are opportunistic foodborne human pathogens that can cause rare but serious diseases in neonates and immune-compromised infants (Iversen et al, 2008; Kucerova et al, 2011; Joseph et al, 2012a). In our previous studies, C. sakazakii , C. malonaticus , and C. dublinensis were three prevalent species in food, however, we have never isolated C. universalis and C. condimenti strains (Xu et al, 2015; Ling et al, 2018; Li et al, 2019). In total, five C. turicensis and one C. muytjensii strains were isolated from vegetables and ready-to-eat foods (Xu et al, 2015; Ling et al, 2018) and we have successfully performed CRISPR arrays on these isolates using the same primers used for C. sakazakii .…”
Section: Discussionmentioning
confidence: 65%
“…All strains belonged to the large-scale and systematic investigation on the prevalence of Cronobacter spp. in food in China, and detailed information about these strains, including O serotypes, STs, and antibiotic-resistance profiles, are provided in Supplementary Data Sheets 1–3 (Zeng et al, 2017, 2018b; Ling et al, 2018; Li et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cronobacter spp. are opportunistic foodborne pathogens that can cause severe infections in neonates and infants through the ingestion of contaminated PIF; therefore, they are of global interest to human health (Forsythe et al, 2014; Fei et al, 2018a; Li et al, 2019). Results of this study suggest that should Cronobacter be detected in clean area or quasi-clean areas, measures must be immediately implemented to prevent contamination of the end products’ subsequent greater contamination of the processing environment (Pei et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the detection rate of Cronobacter spp. is 17.54% (37 positive in 211 samples) in Flammulina velutipes from 44 cities in China [10], indicating that the detection of F. velutipes contamination should be strengthened to avoid food safety issues.…”
Section: Introductionmentioning
confidence: 99%